PRECLINICAL DEVELOPMENT OF A CHIMERIC YELLOW FEVER / TICK-BORNE ENCEPHALITIS VIRUS AS A CANDIDATE VACCINE - Kulatay , T.; Sedova, E.; Shevtsov, A.; Zauatbayeva, G.; Ingirbay, B.; Keyer, V.; Shakhmanova, Zh.; Zhumabekova, M.; Abduraimov , Ye.; Rsaliyev, A.; Sikhayeva, N.; Kozlova , I.; et al. (Eurasian Journal of Applied Biotechnology, 2025)
Tick-borne encephalitis virus (TBEV) is a reemerging pathogen in Kazakhstan. Despite the availability of inactivated TBEV vaccines produced abroad, their reliance on complex multi-dose regimens and frequent boosters limits their implementation for routine use in Kazakhstan. New technologies, including chimerization of different Flavivirus species, enable the development of vaccine candidates which require only a single dose to achieve long-lasting immunity. The ChimeriVax platform leverages the efficient replication machinery of the yellow fever virus (YFV) 17D vaccine strain engineered to express the structural proteins of a different flavivirus. In this work, the ChimeriVax YFV/TBEV virus was created by replacing the prM-E genes in the YFV genome with the prM-E genes of TBEV. Preclinical evaluation demonstrated robust replication ( 10^8 focus-forming units, FFU/mL) in cell cultures and genetic stability over multiple passages. In murine models, the chimeric virus elicited transient viremia (peaking at 10^4 FFU/mL) without mortality even at high doses (10^5 FFU). Immunization induced potent neutralizing antibodies (geometric mean titer: 4,076) and robust cellular immunity, marked by production of the cytokines IFN-γ, TNF-α, and IL-2 upon antigen stimulation. These results position the ChimeriVax YFV/TBEV virus as a promising vaccine candidate.